A preparation process of lithium iron phosphate electrode material

Through the chemical esterification polymerization reaction of polyethylene glycol and diacyl chloride intermediate, a polyethylene glycol copolymer template agent is prepared, and a highly dispersible lithium iron phosphate precursor is generated through complexation and self-assembly of ferric nitrate, lithium hydroxide and ammonium dihydrogen phosphate, which solves the problem of small specific surface area of ​​lithium iron phosphate electrode material and realizes a lithium iron phosphate electrode material with high specific surface area and high charge and discharge capacity.

CN119118088BActive Publication Date: 2025-04-11SICHUAN TIANLI LITHIUM ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411256080.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-04-11
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The specific surface area of ​​lithium iron phosphate electrode material is small, resulting in low charge and discharge capacity and poor rate performance.

Method used

By performing chemical esterification polymerization reaction with polyethylene glycol and diacyl chloride intermediates, a polyethylene glycol copolymer template agent was prepared, and based on it, the complexing and self-assembly of ferric nitrate, lithium hydroxide and ammonium dihydrogen phosphate was generated to form a highly dispersible lithium iron phosphate precursor, and finally, after high temperature calcination, carbon-coated lithium iron phosphate was calcined.

Benefits of technology

The specific surface area and total pore volume of the lithium iron phosphate electrode material are improved, the contact with the electrolyte is enhanced, the electrochemical active site is improved, the migration of lithium ions is promoted, and the charge and discharge capacity and rate performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium iron phosphate, and discloses a preparation process of lithium iron phosphate electrode material. The present invention utilizes polyethylene glycol and diacyl chloride intermediate chemical esterification polymerization reaction to obtain polyethylene glycol copolymer template. Ferric nitrate, lithium hydroxide and ammonium dihydrogen phosphate are used as precursors of lithium iron phosphate, and iron ions, lithium hydroxide and phosphate anions are self-assembled on the molecular chain of the polyethylene glycol copolymer template to generate a highly dispersible lithium iron phosphate precursor, which is calcined at high temperature to generate carbon-coated lithium iron phosphate with good dispersibility and high specific surface area. The more fully in contact with the electrolyte, the more electrochemically active sites, the faster the migration of lithium ions during the charge and discharge process, and the better the charge and discharge capacity, rate performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium iron phosphate, and in particular to a preparation process of a lithium iron phosphate electrode material. Background Art

[0002] In recent years, energy problems have become increasingly severe, and the development of green and environmentally friendly energy conversion devices has become a research hotspot. Lithium-ion batteries have the advantages of high energy density, long cycle life, and environmental friendliness, and have received extensive attention and research. The positive electrode material plays a decisive role in the performance of lithium-ion batteries, and the main materials are lithium iron phosphate, lithium cobalt manganese oxide, and lithium nickel cobalt manganese oxide. Among them, lithium iron phosphate has a simple preparation method, excellent cycle performance, good thermal stability, and has good practical applications.

[0003] Improving the charge and discharge capacity, rate performance and other properties of lithium iron phosphate cathode materials is a research hotspot. When preparing lithium iron phosphate, adding polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone and the like as surfactants and templates can play a role in regulating the growth of lithium iron phosphate structure and adjusting the morphology; and using organic carbon sources to carbon-coat lithium iron phosphate can obtain lithium iron phosphate particles with small particle size and high dispersibility, which is beneficial to improving its specific surface area and electrochemical performance. Summary of the invention

[0004] The invention solves the problems of small specific surface area, low specific capacity and high rate performance of lithium iron phosphate electrode materials.

[0005] Technical solution: A preparation process of lithium iron phosphate electrode material:

[0006] Step A, adding N,N-dimethylformamide, polyethylene glycol in a molar ratio of 1:(2-2.2):(1-1.2), triethylamine, and a diacyl chloride intermediate into a flask, stirring to carry out an esterification reaction, distilling under reduced pressure and washing the product with acetone, then adding it to water to carry out anhydride hydrolysis reaction, heating and evaporating the precipitate, filtering, washing with acetone, and drying to obtain a polyethylene glycol copolymer template agent.

[0007] Step B, add water, polyethylene glycol copolymer template, and ferric nitrate into a flask, stir to carry out a complexing process, then add ammonium dihydrogen phosphate, stir and add lithium hydroxide, control the ratio of polyethylene glycol copolymer template, iron salt, lithium hydroxide, and ammonium dihydrogen phosphate to (300-700) g:1 mol:1 mol:1 mol; after stirring, add ammonia water dropwise, heat and stir until a sol is formed, place the material in a heating box after aging, dry and remove water at 90°C, grind the product, and then place it in a tubular furnace, calcine in a nitrogen atmosphere, and cool to obtain a carbon / lithium iron phosphate material.

[0008] Step C, dispersing the carbon / lithium iron phosphate material, the conductive agent, and the binder in N-methylpyrrolidone, stirring to form a slurry, and then coating it on the surface of the current collector, drying, and punching it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0009] The diacyl chloride intermediate has the following structural formula (I):

[0010] Formula (I).

[0011] Furthermore, the molecular weight of the polyethylene glycol in step A is 400-1000.

[0012] Furthermore, in step A, the esterification reaction is carried out at room temperature for 18-24 hours; and the anhydride hydrolysis reaction is carried out at 60-75° C. for 12-18 hours.

[0013] Furthermore, in step B, the complexation process is carried out at room temperature for 3-6 hours; the temperature during the stirring process to form a sol-like state is 80-90° C.; and the aging is performed by standing at room temperature for 18-24 hours.

[0014] Furthermore, in step B, ammonia water is added dropwise to adjust the pH to 9-10, and the mass fraction of ammonia water is 20-25%.

[0015] Furthermore, the calcination process in step B is to first heat the temperature to 350-400° C., keep the temperature for 2-3 hours, and then heat the temperature to 700-800° C., and keep the temperature for 4-5 hours.

[0016] Furthermore, in step C, the mass ratio of carbon / lithium iron phosphate material, conductive agent, and binder is 8:1:1; the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, and the current collector is aluminum foil.

[0017] Furthermore, the preparation process of the diacyl chloride intermediate is as follows: nitrogen is introduced into a flask, toluene, DL-aspartic acid, 4-dimethylaminopyridine, and trimellitic anhydride chloride are added in a molar ratio of 1: (0.035-0.042): (1-1.1), heated to 35-50°C, reacted for 6-12 hours, distilled under reduced pressure, the product was recrystallized from dichloromethane, the obtained product was added to thionyl chloride, heated to 65-70°C, reacted for 3-4 hours, distilled under reduced pressure, and dried to obtain the diacyl chloride intermediate.

[0018] Technical effect: The present invention utilizes polyethylene glycol and diacyl chloride intermediate chemical esterification polymerization reaction to obtain polyethylene glycol copolymer template agent. Ferric nitrate, lithium hydroxide and ammonium dihydrogen phosphate are used as precursors of lithium iron phosphate, and polyethylene glycol copolymer is used as template agent. Its molecular side chain contains phthalic acid groups, which can react with iron ions to form a complex coordination effect, adsorb iron ions on the molecular chain of polyethylene glycol copolymer template agent, and play a role in dispersing iron ions. Then, iron ions, lithium hydroxide and phosphate anions self-assemble on the molecular chain of polyethylene glycol copolymer template agent to generate highly dispersible lithium iron phosphate precursor. Finally, after high-temperature calcination, polyethylene glycol copolymer is used as template agent to play a structural guiding role, and lithium iron phosphate with good dispersibility and high specific surface area is generated. The specific surface area and total pore volume are larger. At the same time, during the high-temperature calcination process, the high-carbon content benzene ring structure in the copolymer template agent undergoes pyrolysis and carbonization, forming a stable carbon layer on the surface of lithium iron phosphate, thereby forming carbon-coated lithium iron phosphate.

[0019] The carbon / lithium iron phosphate material of the present invention has a higher specific surface area, is more fully in contact with the electrolyte, has more electrochemical active sites, can accelerate the migration of lithium ions during the charge and discharge process, and is conducive to improving the charge and discharge capacity. In addition, the surface of the lithium iron phosphate contains a stable carbon layer structure, which can improve the conductivity of the lithium iron phosphate electrode material. At the same time, the carbon coating can inhibit the growth and agglomeration of lithium iron phosphate particles and improve its dispersion performance. At the same time, the carbon coating can alleviate the effects of volume expansion and improve the rate performance and cycle stability. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] Example 1

[0022] Introduce nitrogen, 80 mL toluene, 80 mmol DL-aspartic acid, 3.36 mmol 4-dimethylaminopyridine, 80 mmol trimellitic anhydride chloride into the flask, heat to 35 ° C, react for 12 hours, distill under reduced pressure, recrystallize the product in dichloromethane, add the obtained product to 200 mL thionyl chloride, heat to 65 ° C, react for 3 hours, distill under reduced pressure, and dry to obtain a diacyl chloride intermediate. The reaction formula is:

[0023]

[0024] Example 2

[0025] Nitrogen, 100 mL of toluene, 80 mmol of DL-aspartic acid, 2.8 mmol of 4-dimethylaminopyridine, and 88 mmol of trimellitic anhydride chloride were introduced into the flask, and the mixture was heated to 50°C, reacted for 6 h, and distilled under reduced pressure. The product was recrystallized in dichloromethane, and the obtained product was added to 180 mL of thionyl chloride, heated to 70°C, reacted for 3 h, and distilled under reduced pressure and dried to obtain a diacyl chloride intermediate.

[0026] Example 3

[0027] (1) Add 500 mL of N,N-dimethylformamide, 50 mmol of polyethylene glycol 400, 100 mmol of triethylamine, and 50 mmol of diacyl chloride intermediate (the same preparation method as in Example 1) to a flask, stir at room temperature for esterification reaction for 24 hours, distill under reduced pressure, wash the product with acetone, then add it to water, heat to 70°C, perform anhydride hydrolysis reaction for 18 hours, heat and evaporate the precipitate, filter, wash with acetone, and dry to obtain a polyethylene glycol copolymer template agent. The reaction formula is as follows:

[0028]

[0029] (2) Add 100 mL of water, 12 g of polyethylene glycol copolymer template, and 40 mmol of ferric nitrate to a flask, stir at room temperature for complexation for 4 h, then add 40 mmol of ammonium dihydrogen phosphate, stir and add 40 mmol of lithium hydroxide, stir and add 20% by mass ammonia water to adjust the pH to 10, heat to 90 ° C, and stir until a sol is formed. After cooling, let it stand and age at room temperature for 24 h. Place the material in a heating box, dry and remove water at 90 ° C, grind the product, and then place it in a tubular furnace in a nitrogen atmosphere at a heating rate of 5 ° C / min. First, heat to 400 ° C, keep warm and calcine for 2 h, then heat to 750 ° C, keep warm for 5 h, cool, and obtain a carbon / lithium iron phosphate material.

[0030] (3) Disperse 80 g of carbon / lithium iron phosphate material, 10 g of conductive carbon black, and 10 g of binder polyvinylidene fluoride in N-methylpyrrolidone, stir to form a slurry, and then coat it on the surface of an aluminum foil current collector, dry it, and punch it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0031] Example 4

[0032] (1) Add 800 mL of N,N-dimethylformamide, 50 mmol of polyethylene glycol 800, 110 mmol of triethylamine, and 60 mmol of diacyl chloride intermediate (prepared in the same manner as in Example 1) into a flask, stir at room temperature for esterification reaction for 18 h, distill under reduced pressure, wash the product with acetone, then add it to water, heat to 60°C, perform an acid anhydride hydrolysis reaction for 18 h, heat and evaporate to precipitate, filter, wash with acetone, and dry to obtain a polyethylene glycol copolymer template agent.

[0033] (2) Add 120 mL of water, 12 g of polyethylene glycol copolymer template, and 40 mmol of ferric nitrate to a flask, stir at room temperature for complexation for 6 hours, then add 40 mmol of ammonium dihydrogen phosphate, stir and add 40 mmol of lithium hydroxide, stir and add 20% ammonia water to adjust the pH to 9, heat to 90°C, and stir until a sol is formed. After cooling, let it stand and age at room temperature for 18 hours. Place the material in a heating box, dry and remove water at 90°C, grind the product, and then place it in a tubular furnace in a nitrogen atmosphere at a heating rate of 5°C / min. First, heat to 350°C, keep warm and calcine for 3 hours, then heat to 700°C, keep warm for 5 hours, and cool to obtain a carbon / lithium iron phosphate material.

[0034] (3) Disperse 80 g of carbon / lithium iron phosphate material, 10 g of conductive carbon black, and 10 g of binder polyvinylidene fluoride in N-methylpyrrolidone, stir to form a slurry, and then coat it on the surface of an aluminum foil current collector, dry it, and punch it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0035] Example 5

[0036] (1) Add 800 mL of N,N-dimethylformamide, 50 mmol of polyethylene glycol 1000, 100 mmol of triethylamine, and 50 mmol of diacyl chloride intermediate (prepared in the same manner as in Example 1) into a flask, stir at room temperature for esterification reaction for 24 h, distill under reduced pressure, wash the product with acetone, then add it to water, heat to 75°C, perform anhydride hydrolysis reaction for 12 h, heat and evaporate to precipitate, filter, wash with acetone, and dry to obtain a polyethylene glycol copolymer template agent.

[0037] (2) Add 120 mL of water, 12 g of polyethylene glycol copolymer template, and 40 mmol of ferric nitrate to a flask, stir at room temperature for complexation for 3 h, then add 40 mmol of ammonium dihydrogen phosphate, stir and add 40 mmol of lithium hydroxide, stir and add 25% by mass of ammonia water to adjust the pH to 10, heat to 80 ° C, and stir until a sol is formed. After cooling, let it stand and age at room temperature for 24 h. Place the material in a heating box, dry and remove water at 90 ° C, grind the product, and then place it in a tubular furnace in a nitrogen atmosphere at a heating rate of 5 ° C / min. First, heat to 400 ° C, keep warm and calcine for 2 h, then heat to 800 ° C, keep warm for 4 h, cool, and obtain a carbon / lithium iron phosphate material.

[0038] (3) Disperse 80 g of carbon / lithium iron phosphate material, 10 g of conductive carbon black, and 10 g of binder polyvinylidene fluoride in N-methylpyrrolidone, stir to form a slurry, and then coat it on the surface of an aluminum foil current collector, dry it, and punch it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0039] Example 6

[0040] (1) Add 100 mL of water, 20 g of polyethylene glycol copolymer template (prepared in the same manner as in Example 3), and 40 mmol of ferric nitrate to a flask, stir at room temperature for complexation for 4 h, then add 40 mmol of ammonium dihydrogen phosphate, stir and add 40 mmol of lithium hydroxide, stir and drop 20% ammonia water to adjust the pH to 10, heat to 90°C, and stir until a sol is formed. After cooling, stand and age at room temperature for 24 h, place the material in a heating box, dry and remove water at 90°C, grind the product, and then place it in a tubular furnace in a nitrogen atmosphere at a heating rate of 5°C / min, first heat to 400°C, keep warm and calcine for 2 h, then heat to 750°C, keep warm for 5 h, and cool to obtain a carbon / lithium iron phosphate material.

[0041] (2) Disperse 80 g of carbon / lithium iron phosphate material, 10 g of conductive carbon black, and 10 g of binder polyvinylidene fluoride in N-methylpyrrolidone, stir to form a slurry, and then coat it on the surface of an aluminum foil current collector, dry it, and punch it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0042] Example 7

[0043] (1) Add 100 mL of water, 20 g of polyethylene glycol copolymer template (prepared in the same manner as in Example 3), and 40 mmol of ferric nitrate to a flask, stir at room temperature for complexation for 4 h, then add 40 mmol of ammonium dihydrogen phosphate, stir and add 40 mmol of lithium hydroxide, stir and drop 20% ammonia water to adjust the pH to 10, heat to 90°C, and stir until a sol is formed. After cooling, stand and age at room temperature for 24 h, place the material in a heating box, dry and remove water at 90°C, grind the product, and then place it in a tubular furnace in a nitrogen atmosphere at a heating rate of 5°C / min, first heat to 400°C, keep warm and calcine for 2 h, then heat to 750°C, keep warm for 5 h, and cool to obtain a carbon / lithium iron phosphate material.

[0044] (2) Disperse 80 g of carbon / lithium iron phosphate material, 10 g of conductive carbon black, and 10 g of binder polyvinylidene fluoride in N-methylpyrrolidone, stir to form a slurry, and then coat it on the surface of an aluminum foil current collector, dry it, and punch it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0045] Comparative Example 1

[0046] (2) Add 100 mL of water, 12 g of polyethylene glycol 400, and 40 mmol of ferric nitrate to a flask, stir at room temperature for complexation for 4 h, then add 40 mmol of ammonium dihydrogen phosphate, stir and add 40 mmol of lithium hydroxide, stir and add 20% by mass of ammonia water to adjust the pH to 10, heat to 90 ° C, and stir until a sol is formed. After cooling, let it stand and age at room temperature for 24 h. Place the material in a heating box, dry and remove water at 90 ° C, grind the product, and then place it in a tubular furnace in a nitrogen atmosphere at a heating rate of 5 ° C / min. First, heat to 400 ° C, keep warm and calcine for 2 h, then heat to 750 ° C, keep warm for 5 h, cool, and obtain a carbon / lithium iron phosphate material.

[0047] (3) Disperse 80 g of carbon / lithium iron phosphate material, 10 g of conductive carbon black, and 10 g of binder polyvinylidene fluoride in N-methylpyrrolidone, stir to form a slurry, and then coat it on the surface of an aluminum foil current collector, dry it, and punch it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0048] Comparative Example 2

[0049] (1) Add 500 mL of N,N-dimethylformamide, 50 mmol of polyethylene glycol 400, 100 mmol of triethylamine, and 50 mmol of terephthaloyl chloride into a flask, stir at room temperature for esterification reaction for 24 hours, distill under reduced pressure, wash the product with acetone, then add it to water, heat to 70°C, carry out anhydride hydrolysis reaction for 18 hours, heat and evaporate the precipitate, filter it, wash it with acetone, and dry it to obtain a polyethylene glycol copolymer template agent.

[0050] (2) Add 100 mL of water, 12 g of polyethylene glycol copolymer template, and 40 mmol of ferric nitrate to a flask, stir at room temperature for complexation for 4 h, then add 40 mmol of ammonium dihydrogen phosphate, stir and add 40 mmol of lithium hydroxide, stir and add 20% by mass ammonia water to adjust the pH to 10, heat to 90 ° C, and stir until a sol is formed. After cooling, let it stand and age at room temperature for 24 h. Place the material in a heating box, dry and remove water at 90 ° C, grind the product, and then place it in a tubular furnace in a nitrogen atmosphere at a heating rate of 5 ° C / min. First, heat to 400 ° C, keep warm and calcine for 2 h, then heat to 750 ° C, keep warm for 5 h, cool, and obtain a carbon / lithium iron phosphate material.

[0051] (3) Disperse 80 g of carbon / lithium iron phosphate material, 10 g of conductive carbon black, and 10 g of binder polyvinylidene fluoride in N-methylpyrrolidone, stir to form a slurry, and then coat it on the surface of an aluminum foil current collector, dry it, and punch it into an electrode sheet to obtain a lithium iron phosphate electrode material.

[0052] The specific surface area and pore volume of the carbon / lithium iron phosphate material were tested by a specific surface area analyzer and nitrogen adsorption-desorption isotherm method.

[0053] Specific surface area (m2 / g) Total pore volume (cm3 / g) Example 3 63.2 0.069 Example 4 69.0 0.083 Example 5 74.5 0.094 Example 6 92.1 0.118 Example 7 79.6 0.097 Comparative Example 1 22.1 0.034 Comparative Example 2 21.7 0.031

[0054] After testing, when preparing the carbon / lithium iron phosphate material, Examples 3-7 added a polyethylene glycol copolymer template agent, whose molecular side chain contains phthalic acid groups, which can react with iron ions to form a complex coordination effect, adsorb the iron ions on the molecular chain of the polyethylene glycol copolymer template agent, and play a role in dispersing the iron ions. Then the iron ions, lithium hydroxide and phosphate anions self-assemble on the molecular chain of the polyethylene glycol copolymer template agent to generate a highly dispersible lithium iron phosphate precursor. Finally, after high-temperature calcination, the polyethylene glycol copolymer is used as a template agent to play a structural guiding role to generate lithium iron phosphate with good dispersibility and high specific surface area. The specific surface area and total pore volume are larger. At the same time, during the high-temperature calcination process, the high-carbon benzene ring structure in the copolymer template agent undergoes pyrolysis and carbonization to form a stable carbon layer on the surface of the lithium iron phosphate, thereby forming carbon-coated lithium iron phosphate.

[0055] In comparative example 1, polyethylene glycol is used as a template agent, and in comparative example 2, polyethylene glycol 400 and terephthaloyl chloride are used for esterification polymerization to obtain a polyethylene glycol copolymer as a template agent. Both do not contain phthalic acid groups, and the complexing and coordination effect on iron ions is poor, making it difficult to disperse iron ions, and it is impossible to make iron ions self-assemble with lithium hydroxide and phosphate anions on the molecular chain of the polyethylene glycol copolymer template agent. Polyethylene glycol is difficult to play the role of a template agent and a structure guide, and the specific surface area of ​​the obtained lithium iron phosphate is small.

[0056] The lithium iron phosphate electrode material was used as the positive electrode, the lithium sheet was used as the negative electrode, the polypropylene microporous membrane was used as the separator, the 1 mol / L lithium hexafluorophosphate solution was used as the electrolyte, and the solvent was a mixed solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate. The button cell was formed in an argon glove box. The charge and discharge performance was tested using a blue battery tester. The test temperature was room temperature, and the charge and discharge current was 0.1-2C. The charge and discharge voltage range was 2.0-4.2V.

[0057] Table 2 Charging capacity test when the charging and discharging current is 0.1C

[0058] First charge capacity (mAh / g) First discharge capacity (mAh / g) Coulomb efficiency (%) Example 3 151.1 147.2 97.42 Example 4 157.9 151.9 96.20 Example 5 162.5 156.8 96.49 Example 6 171.4 169.0 98.60 Example 7 168.2 166.7 99.11 Comparative Example 1 133.8 126.0 94.17 Comparative Example 2 145.7 140.3 96.29

[0059] Table 3 Charging capacity test when the charging and discharging current is 2C

[0060] First charge capacity (mAh / g) First discharge capacity (mAh / g) Coulomb efficiency (%) Example 3 143.2 139.0 97.07 Example 4 149.3 143.3 95.93 Example 5 153.8 146.4 95.19 Example 6 162.7 160.6 98.71 Example 7 160.1 158.0 98.69 Comparative Example 1 124.6 114.7 92.05 Comparative Example 2 136.9 130.5 95.33

[0061] After testing, the lithium iron phosphate electrode materials of Examples 3-7 have good charge and discharge specific capacity and high coulomb efficiency at currents of 0.1C and 2C. This is because the carbon / lithium iron phosphate material has a higher specific surface area, more complete contact with the electrolyte, and more electrochemically active sites, which can accelerate the migration of lithium ions during the charge and discharge process, and is conducive to improving the charge and discharge capacity. In addition, the surface of lithium iron phosphate contains a stable carbon layer structure, which can improve the conductivity of the lithium iron phosphate electrode material. At the same time, the carbon coating can inhibit the growth and agglomeration of lithium iron phosphate particles and improve its dispersion performance. At the same time, the carbon coating can alleviate the effects of volume expansion and improve the rate performance and cycle stability.

[0062] The specific surface area of ​​the carbon / lithium iron phosphate materials in Comparative Examples 1 and 2 is relatively small, and the charge-discharge specific capacity and rate performance are significantly lower than those in the embodiment. However, the charge-discharge specific capacity and rate performance of Comparative Example 2 are higher than those in Example 1, which may be because the polyethylene glycol copolymer template contains a high carbon content benzene ring structure, which undergoes pyrolysis and carbonization, forming a stable carbon layer on the surface of the lithium iron phosphate, forming a stable carbon-coated lithium iron phosphate, which is beneficial to improving the charge-discharge specific capacity and rate performance.

[0063] The above are only preferred specific implementations of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A process for preparing a lithium iron phosphate electrode material, characterized in that: The preparation process comprises the following steps: Step A, adding N,N-dimethylformamide, polyethylene glycol, triethylamine, and a diacyl chloride intermediate in a molar ratio of 1:(2-2.2):(1-1.2) into a flask, stirring to carry out an esterification reaction, distilling under reduced pressure, washing the product with acetone, then adding it to water to carry out anhydride hydrolysis reaction, heating and evaporating to precipitate a precipitate, filtering, washing, and drying to obtain a polyethylene glycol copolymer template agent; Step B, add water, polyethylene glycol copolymer template, and ferric nitrate into a flask, stir to carry out a complexing process, then add ammonium dihydrogen phosphate, stir and add lithium hydroxide, control the ratio of polyethylene glycol copolymer template, iron salt, lithium hydroxide, and ammonium dihydrogen phosphate to be (300-700) g:1 mol:1 mol:1 mol; after stirring, add ammonia water dropwise, heat and stir until a sol is formed, place the material in a heating box after aging, dry and remove water at 90° C., grind the product, and then place it in a tubular furnace, calcine in a nitrogen atmosphere, and cool to obtain a carbon / lithium iron phosphate material; Step C, dispersing the carbon / lithium iron phosphate material, the conductive agent, and the binder in N-methylpyrrolidone, stirring to form a slurry, and then coating it on the surface of the current collector, drying, and punching it into an electrode sheet to obtain a lithium iron phosphate electrode material; The diacyl chloride intermediate has the following structural formula (I): Formula (I).

2. The process for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: The molecular weight of the polyethylene glycol in step A is 400-1000.

3. The process for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: In the step A, the esterification reaction is carried out at room temperature for 18-24 hours; and the anhydride hydrolysis reaction is carried out at 60-75° C. for 12-18 hours.

4. The process for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: In the step B, the complexing process is carried out at room temperature for 3-6 hours; the temperature during the stirring process to form a sol-like state is 80-90° C.; and the aging is carried out by standing at room temperature for 18-24 hours.

5. The process for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: In the step B, ammonia water is added dropwise to adjust the pH to 9-10, and the mass fraction of ammonia water is 20-25%.

6. The process for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: The calcination process in step B is to first heat the temperature to 350-400° C., keep the temperature for 2-3 hours, then heat the temperature to 700-800° C., and keep the temperature for 4-5 hours.

7. The process for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: In the step C, the mass ratio of the carbon / lithium iron phosphate material, the conductive agent, and the binder is 8:1:1; the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, and the current collector is aluminum foil.

8. The process for preparing the lithium iron phosphate electrode material according to claim 1, characterized in that: The preparation process of the diacyl chloride intermediate is as follows: nitrogen is introduced into a flask, toluene, DL-aspartic acid, 4-dimethylaminopyridine, and trimellitic anhydride chloride are added, the mixture is heated to 35-50° C., reacted for 6-12 hours, distilled under reduced pressure, and recrystallized; the obtained product is added to thionyl chloride, heated to 65-70° C., reacted for 3-4 hours, distilled under reduced pressure, and dried to obtain the diacyl chloride intermediate.

9. The process for preparing the lithium iron phosphate electrode material according to claim 8, characterized in that: The molar ratio of DL-aspartic acid, 4-dimethylaminopyridine and trimellitic anhydride chloride is 1:(0.035-0.042):(1-1.1).

Citation Information

Patent Citations

  • All-solid-state polymer electrolyte, preparation method thereof, and all-solid-state lithium ion battery

    CN109768320A

  • Graphene modified-carbon coated lithium iron phosphate material, preparation method thereof and solid-state lithium ion battery

    CN114497556A